Readings in the Concept and Measurement of Income (Book). - Lemke, Kenneth W. (The Accounting Review, 1987)
Abstract Reviews the book "Readings in the Concept and Measurement of Income," edited by R.H. Parker, G.C. Harcourt and G. Whittington.